Timeline of autumn phenology in temperate deciduous trees. (27th April 2020) - Dox, Inge; Gričar, Jožica; Marchand, Lorène J; Leys, Sebastien; Zuccarini, Paolo; Geron, Charly; Prislan, Peter; Mariën, Bertold; Fonti, Patrick; Lange, Holger; Peñuelas, Josep; Van den Bulcke, Jan; et al.
Abstract: Cessation of xylem formation or wood growth (CWG) and onset of foliar senescence (OFS) are key autumn phenological events in temperate deciduous trees. Their timing is fundamental for the development and survival of trees, ecosystem nutrient cycling and the seasonal exchange of matter and energy between the biosphere and atmosphere, and affects the impact and feedback of forests to global change. A large-scale experimental effort and improved observational methods have allowed us to compare the timing of CWG and OFS for different deciduous tree species in Western Europe, particularly in silver birch, a pioneer species, and European beech, a late-succession species, at stands of different latitudes, of different levels of site fertility, for 2 years with contrasting meteorological and drought conditions, i.e., the low moderately dry 2017 and the extremely dry 2018. Specifically, we tested whether foliar senescence started before, after or concurrently with CWG. Onset of foliar senescence and CWG occurred generally between late September and early November, with larger differences across species and sites for OFS. Foliar senescence started concurrently with CWG in most cases, except for the drier 2018 and, for beech, at the coldest site, where OFS occurred significantly later than CWG. The behavior of beech in Spain, the southern edge of its European distribution, was unclear, with no CWG, but very low wood growth at the time of OFS. Our study suggests that OFS is generally triggered by the same drivers of CWG or when wood growth decreases in late summer, indicating an overarching mechanism of sink limitation as a possible regulator of the timing of foliar senescence.